Effect of regional variation on the total flavonoid level of ethanol extract of mangosteen (Garcinia mangostana) peels - Any Guntarti; Juniati Annisa; Mulki Mughniy; Fitria Rizqi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background : Currently, traditional medicines have been widely used by the public. One of them is mangosteen peel. Extract of mangosteen peel contains alkaloids, glycosides, steroids, flavonoids, polyphenols, and tannins. In order to ensure the quality of the extract so that its chemical content can be guaranteed, it is necessary to standardize the quality of the extract that consists of specific parameters. Objective : This study aims to determine the specific parameters using Thin-Layer Chromatography (TLC) and total flavonoid level of the ethanol extract of mangosteen peel from Kalimantan, Java, and Sumatra. Methods : This research was an explorative study. Extraction technique used was maceration with 70% ethanol solvent. The tested specific parameters, namely the identity of the extract with TLC and total flavonoid level, were determined afterward using visible spectrophotometry with the AlCl3 reagent. Results: The result of the qualitative test with TLC showed that the extract of mangosteen peel contains flavonoids, terpenoids, and anthraquinones. Total flavonoid level of ethanol extract of mangonsteen peel from Kalimantan, Java, and Sumatra were (0.301 ± 0.009); (0.398 ± 0.015); (0,747 ± 0,010) mg QE/g extract, respectively. Conclusion : Extract of mangosteen peel contains flavonoids, terpenoids, and anthraquinones. Total flavonoid level of ethanol extract of mangonsteen peel from Kalimantan, Java, and Sumatra were (0.301 ± 0.009); (0.398 ± 0.015); (0,747 ± 0,010) mg QE/g of extract, respectively.